Damping Evaluation of Linseed Oil-Based Engineering Elastomers by Vibration Response Method. (23rd February 2014) - Das, Rakesh; Kumar, Rajesh; Kundu, P. P.
Abstract : A low cost experimental setup has been fabricated for evaluation of vibration damping properties of a variety of elastomers developed from linseed oil. Free and forced vibration principles were utilized in this experimental setup. Under forced vibration, the shear loss factor varies from 0.37 to 1.03 at 2nd bending vibration mode and 0.43 to 0.99 at 3rd bending vibration mode for different elastomers. The loss factor varies from 0.52 to 0.94 under free vibration. The loss factors determined by both forced and free vibration techniques are in good agreement with the loss factors obtained from dynamic mechanical analysis. The ultimate tensile strength and Young's modulus of the elastomers vary from 0.37 to 3.71 MPa and 0.27 to 10.27 MPa, respectively, whereas these properties in compression are in the range of 3.1 to 72.9 MPa and 1.5 to 30.1 MPa, respectively. Thus, these elastomers are mechanically stable for vibration damping applications.